Electrocatalytic hydrogen evolution reaction with metallophthalocyanines modified with click electrochemistry - ÖZKAYA, ALİ RIZA; KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Cobalt and zinc phthalocyanines bearing terminal alkyne groups (TA-CoPc and TA-ZnPc) were electrochemically characterized in order to determine their functionalities for practical usages as effective electrocatalysts. Observation of multi-electron and metal and/or ring based reduction reactions at low potentials indicated the worthy of these complexes as functional materials. Shifts of proton reduction potentials toward more positive values in solutions involving MPc indicated homogeneous electrocatalytic activities of the complexes for hydrogen evolution reaction (HER). For practical usage as heterogeneous electrocatalysts for HER, electrodes were constructed with a new electrode modification technique, click electrochemistry, with which TA-CoPc and TA-ZnPc complexes were bonded to azido functionalized polyaniline (PANI-N-3) electropolymerized on electrodes. The modified Glassy Carbon Electrode (GCE)/PANI-N-3/TA-CoPc and GCE/PANI-N-3/TA-ZnPc electrodes were characterized using voltammetric techniques and electrochemical impedance spectroscopy (EIS), then tested as heterogeneous electrocatalyst for HER. GCE/PANI-N-3/TA-CoPc electrodes especially decrease the over-potential of the bare electrode about 216 mV and increase the efficiency of the electrode about 32 fold at low pHs. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Electrocatalyst; Hydrogen evolution reaction; Phthalocyanine; Click electrochemistry; WATER ELECTROLYSIS; OXYGEN REDUCTION; TETRASULFONATED PHTHALOCYANINES; COBALT PHTHALOCYANINES; PROTON REDUCTION; ELECTRODES; COMPLEXES; SPECTROELECTROCHEMISTRY; 4-AZIDOANILINE; MONONUCLEAR